Distinctive characteristics in adult female howler monkeys (Alouatta palliata mexicana) on the Agaltepec island, Veracruz, México - Gisbrecht, Anna; Hernández-Arriaga, Erandi Susana; Hernández-Salazar, Laura Teresa (Therya Notes, 2023)
In primatology, the interest in research on females is growing for a better understanding of aspects like social interactions, maternal care, and female animal health. The correct identification of focal subjects is a major challenge in such studies. Adult female mantled howler monkeys (Alouatta palliata) illustrate well the methodological limitations. During a study on the Agaltepec island in Catemaco, Veracruz, México, we came across this challenge. As a strictly arboreal species howler monkeys are often located at higher levels covered by canopy which reveals only few parts for identification. Also, females with small offspring tend to stay further away from observers, even if fully habituated. In order to be able to begin with accurate data collection, a detailed identification of all adult females was completed. A total of 23 animals was described. The descriptions of the females refer mainly to their hands, feet and tail; the body parts that show signs of coloration. The necessity of the animal recognizability often causes young scientists to despair and leads to the loss of valuable investigation time. To facilitate the next generation of researchers on the Agaltepec island in their data acquisition, we present the detailed composition and description of the resident, adult females. We hope to provide reliable support for an efficient start of new projects.